Knowledge, attitude and practice of cybercrime among secondary school students in Nigeria (2020)
The Internet, which has opened a vast array of possibilities for the young and the old in the social, economic, education, health and other sectors, has been flawed by the rise in internet crimes regarded as unethical use of the computer and internet which could cripple the nation's economy if not given attention. These include cyber fraud (yahoo-yahoo), plagiarism, pornography, and piracy of software. Reports have shown that perpetrators of these cybercrimes have been assumed to be youths usually within the ages of 15 and 30 years. Despite various efforts put in place to address the menace it appears the unwanted practice still persists. It seems that youngsters enter into the practice ignorantly and with confused attitude to it. Therefore, this paper investigated students' awareness of computer ethics, knowledge, attitude to and practice of computer ethics among Junior Secondary School 3 students in Ibadan, Oyo State, Nigeria. The study is a descriptive survey design using with a total of eighty-five (85) participants. The results show that majority of the students were aware of the ethical and unethical use of the computer/internet, few of the respondents are very knowledgeable as regards computer ethics and they have a positive attitude towards computer ethics. Each of the respondents engages in more than two unethical ways of using the computer/internet. The paper concludes that secondary school students engage in unethical use of computer/ internet despite their awareness, knowledge and a show of positive attitude to ethical use of computer/internet. It is recommended that appropriate legal measures should be taken to curb the practice among secondary students in Nigeria.